Asuhan Keperawatan Maternitas pada Pasien dengan Abortus Inkomplit di Ruang Safa Rumah Sakit Aisyiyah Pariaman - Maidawilis Maidawilis; Reza Sentia; Aulia Asman; Yessy Aprihatin (Jurnal Sains dan Kesehatan, 2023)
Abortion is the termination of a pregnancy before 20 weeks of age and can also occur at 12 weeks of gestation or when the fetus weighs less than 500 grams. According to the World Health Organization (WHO), the incidence of abortion in Indonesia is the highest among other Southeast Asian countries, namely 2 million out of 4.2 million people. Incomplete abortion, that is, only part of the conception is removed, what remains is the decidua or placenta. Initially there is bleeding in the decidua basalis, followed by necrosis of the surrounding tissue, then part or all of the products of conception are released. Other complications of incomplete abortion are infection, perforation, and shock. The purpose of this study was to provide nursing care for patients with incomplete abortion in the couch room at Aisyiyah Pariaman Hospital. The research used a descriptive approach in the form of a case study to find out the problem of nursing care in patients with incomplete abortions in the couch room of Aisyiyah Pariaman Hospital with one patient. This research was conducted on 20-24 February 2023, The results of the study after the study found 3 diagnoses, namely: Anxiety related to situational crises,Riskfor hypovolemia related to active fluid lossand Acute pain related to physiological injury,. During the 5 days of the study the patient went home with thesuggestion that the patient could carry out home care and control according to the recommendations from the hospital.